Study on students’ experiences about online teaching during COVID-19 Outbreak - Al-Mohair, Hani; Alwahaishi, Saleh (Technium Social Sciences Journal, 2020)
The online teaching in colleges and universities during the COVID-19 outbreak is one of the challenges faced by faculty and students during this period especially for colleges and universities that meet the quality assurance standards and under the accreditation process. One of the main requirements of quality standards is to carry out a variety of opinion surveys at different stages among different levels of study, analyze, and then provide recommended solutions based on survey findings. Although many researchers have been carried out online teaching, there is no consensus on the impact of a sudden transition from face-to-face learning to online learning especially in community colleges in Saudi Arabia. The purpose of this paper is to present the outcomes of the study on students’ experiences about online teaching during COVID-19 Outbreak. Smart PLS program is used for testing the model and to make sure that the variables are appropriate and the outcomes are valid.